2018
DOI: 10.2741/4660
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet autophagy during energy mobilization lipid homeostasis and protein quality control

Abstract: Lipid droplets (LDs) have well-established functions as sites for lipid storage and energy mobilization to meet the metabolic demands of cells. However, recent studies have expanded the roles of LDs to protein quality control. Lipophagy, or LD degradation by autophagy, plays a vital role not only in the mobilization of free fatty acids (FFAs) and lipid homeostasis at LDs, but also in the adaptation of cells to certain forms of stress including lipid imbalance. Recent studies have provided new mechanistic insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…CMA is a specialized form of selective autophagy, so far characterized only in mammalian cells, and includes a motif-based recognition of damaged proteins by the heat shock cognate protein of 70 kDa (Hsc70) and lysosomal intake mediated by the lysosome-associated membrane protein type 2 (LAMP-2A) [ 236 ]. In contrast, microautophagy enables the uptake of cytoplasmic material by a direct invagination of the lysosomal membrane and it has been characterized in yeast [ 46 , 237 ], while its importance in mammalian cells is still questionable.…”
Section: Lipid Droplets and Autophagy/lipophagymentioning
confidence: 99%
See 3 more Smart Citations
“…CMA is a specialized form of selective autophagy, so far characterized only in mammalian cells, and includes a motif-based recognition of damaged proteins by the heat shock cognate protein of 70 kDa (Hsc70) and lysosomal intake mediated by the lysosome-associated membrane protein type 2 (LAMP-2A) [ 236 ]. In contrast, microautophagy enables the uptake of cytoplasmic material by a direct invagination of the lysosomal membrane and it has been characterized in yeast [ 46 , 237 ], while its importance in mammalian cells is still questionable.…”
Section: Lipid Droplets and Autophagy/lipophagymentioning
confidence: 99%
“…A sudden depletion of glucose in yeast cells activates AMPK-dependent lipid droplet breakdown by microautophagy, i.e., microlipophagy, and provides energy for long-term survival [ 258 ]. Microlipophagy has also been implicated in the management of ER lipid and protein quality control during phospholipid imbalance-induced ER stress [ 46 , 237 ]. It was found that lipid droplets are formed at ER aggregates and act as carriers for the transfer of damaged proteins and toxic lipids from the ER to the vacuole through microlipophagy [ 46 , 237 ].…”
Section: Lipid Droplets and Autophagy/lipophagymentioning
confidence: 99%
See 2 more Smart Citations
“…The cryo-EM study also pointed to the formation of cortical vesicle-like structures, which we believe may correspond to lipid droplets. Since previous studies have shown that the formation of lipid droplets denotes an adaptive response to a chronic lipid imbalance ( Vevea et al, 2015 ; Garcia et al, 2018 ), which is likely to occur in bro1Δ strain because of hampered MVB formation and lipid turnover, we decided to perform a Nile Red staining to visualize the droplets. While during the first hours of induction on galactose-containing medium we observed an overall enhanced lipid droplet biogenesis in all bro1 Δ strains as compared to the respective wild-type strains, the increase was persistent and especially more dense droplets were seen with bro1 Δ cells expressing αAβ 42 G37C or αAβ 42 wt (Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%